The Impact of Corporate Governance Characteristics on the Level of Forward-Looking Information Disclosure: Evidence from the Tehran Stock Exchange - Rezaei Rad, Marzieh; Maranjory, Mehdi; Alikhani , Razieh; Taghipourian , Yosef (Future of Work and Digital Management Journal, 2026)
The purpose of the present study is to examine the impact of corporate governance characteristics on the level of forward-looking information disclosure. In terms of objective, this research is applied in nature and is classified as a descriptive–correlational study. The statistical population consists of all companies listed on the Tehran Stock Exchange during the period from 2018 to 2023. After applying systematic screening criteria, 116 firms were selected as the research sample. Data analysis was conducted using EViews econometric software, and a multivariate linear regression model was employed to test the research hypotheses. The findings indicate that corporate governance characteristics—namely board size, board independence, and audit committee independence—have a positive and statistically significant effect on the level of forward-looking information disclosure, whereas ownership concentration has a negative and statistically significant effect on the level of forward-looking information disclosure.